Optimizing Human Capital through Training, Career Development, and Discipline to Improve Employee Performance: Evidence from South Labuhanbatu Government Office - Afgandhi, Maulana; Hasibuan, Muhammad Irwansyah; Gulo, Nur’ainun (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the effect of training, career development, and work discipline on employee performance. The research is motivated by the need to strengthen human resource capacity in the public sector to deliver optimal services. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through the SmartPLS application. Data were collected through questionnaires distributed to employees of the South Labuhanbatu District Disaster Management Agency. The findings indicate that training has a positive and significant impact on employee performance, showing that relevant, targeted, and continuous training programs can enhance employees’ skills and work productivity. Career development also plays a vital role by motivating employees to improve their performance when clear and structured career pathways are provided. In addition, work discipline contributes significantly to employee performance, as adherence to rules, accountability, and consistency in work behavior strengthen overall performance. These results highlight the importance of integrating training, career development, and work discipline in organizational strategies. The study emphasizes the need for public organizations to design effective training programs, establish structured career development systems, and promote a strong culture of discipline to sustainably improve employee productivity and service quality.